Prevalence of Exclusive Breastfeeding among Adolescent Mothers in Bangkok - Ngamnil, Natthanon; Kaewkiattikun, Kasemsis (Thai Journal of Obstetrics and Gynaecology, 2019)
Objectives: To find the prevalence of exclusive breastfeeding (EBF) among adolescent mothers at 1 to 6 months postpartum and to evaluate the potential factors that encourage 6 months of EBF. Materials and Methods: This prospective descriptive study was conducted from May to December 2016. A total of 192 adolescent mothers were interviewed directly at postpartum and interviewed by phone monthly over six months. The primary outcome was prevalence of EBF at 1 to 6 months postpartum. The secondary outcome was potential factors of 6 months EBF and reasons for discontinuation of EBF before 6 months. Results: The prevalence EBF rates at 1 to 6 months postpartum were 97.4%, 54.7%, 32.3%, 25.5%, 20.8% and 19.8% respectively. The most common reasons for discontinuation of EBF were returning to school or work (58.4%). Significant predicting factors of 6 months EBF were maternal age 17-19 years old (adjust odds ratio (aOR) 5.96, 95% CI 1.62-21.92), marital marriage status (aOR 2.79, 95% CI 1.13-6.86), unemployment / housewives (aOR 10.08, 95% CI 2.00-50.75), and having income (aOR 3.98, 95% CI 1.35-11.72). Conclusion: This study showed that EBF in adolescent mothers for 6 months was 19.8%. The most reasons of discontinuation of EBF before 6 months were returning to school or work. Significant predicting factors for 6 months EBF were maternal age, marital status, occupation and income.